Teachers assistance of Google for education in supporting education 4.0 - Sudiran, S.; Adityo, A. (Journal of Community Service and Empowerment, 2023)
Teachers in the education era 4.0 are asked to be able to do learning that is not limited to space and is full of learning resources electronically and connected to the internet. However, today it is no longer a secret that students who are young learners master technology more than adults who still apply traditional learning methods that are currently deemed less effective. This community service program is carried out with the aim of increasing the ability of teachers to use Google for Education in facing education 4.0 at MTs Muhammadiyah 1 Malang city partner schools where mastery of the use of educational applications can be implemented as a learning support medium. The implementation of this internal community service program uses workshop and mentoring methods. The place of program implementation is at MTs Muhammadiyah 1 Malang city. Meanwhile, the number of participants was six English teachers. The workshop was held for one day and was followed by mentoring for three months to produce a Google for Education based course material design. The result of this internal community service is the production of a mentoring module to improve teacher competence in utilizing the Google application as a medium for teaching English. Through this module teachers can apply their skills in optimally improving student learning outcomes. Based on the data and discussion it can be concluded that the community service has been successfully implemented.